E-learning module on tobacco counselling for students of medicine and dentistry in India: a needs analysis using mixed-methods research - Praveen Kulkarni; Madhu Basavegowda; Chandrashekar B R; Nishath Khanum; Kishor M; Suma S (BMJ Public Health)
Introduction In the background of lack of integrated tobacco counselling training (TCT) in the existing medical and dental curriculum, the present study was undertaken to determine the need for developing an e-learning module on tobacco counselling for students of medicine and dentistry in India.Methods A mixed-method research with a modified exploratory sequential design was undertaken between January and August 2022 in a private medical and a dental college in Southern India, where the qualitative research was done by conducting in-depth interviews with six subject experts and two focus group discussions (FGDs) separately among six medical and six dental interns to identify the gaps in current TCT. Based on the themes from qualitative research, a questionnaire was developed and validated to elicit the knowledge and competence in tobacco counselling. This questionnaire was subsequently used to explore quantitatively the current knowledge and competence in tobacco counselling among the final-year MBBS (bachelor of medicine and bachelor of surgery) and BDS (bachelor of dental surgery) students. The results of the questionnaire study were triangulated with the themes of the qualitative research.Results The qualitative research proffered the lack of structured TCT in the present curriculum and emphasised the need for an integrated, self-paced e-learning tobacco counselling training module (TCTM) in the background of curricular time constraints to accommodate a conventional classroom-based TCTM. During the in-depth interviews and FGDs, the participants suggested including the global burden and pattern of tobacco consumption, tobacco control laws and tobacco counselling methods, as some of the key contents of the module. The quantitative data analysis revealed the lack of knowledge and competence of students in tobacco counselling. The results of the quantitative phase substantiated the themes that emerged from the qualitative phase.Conclusion There is a need for introducing a customised, self-paced, integrated e-learning module on tobacco counselling for the students of medicine and dentistry in India. The e-learning module can be included as a choice-based value addition to the regular curriculum.